The role of intermediaries in selection markets: Evidence from mortgage lending - Jason Allen; Robert Clark; Jean-François Houde; Shaoteng Li; Anna V. Trubnikova (Bank of Canada, 2023)
We study the role of intermediaries (brokers) in the Canadian mortgage market. In this market, consumers can search for quotes in one of two ways: on their own or via a broker. We provide descriptive evidence that borrowers who transact through brokers are different from those who do not. Broker-clients finance larger loans, are more leveraged, and are less creditworthy. After controlling for observable borrower characteristics that might explain these facts, we estimate a model of mortgage demand to disentangle two explanations for why borrowers wind up with these riskier mortgage products: (i) brokers steer borrowers towards products that are more profitable for them, and (ii) borrowers have (unobserved) preferences for riskier loans, i.e., selection on unobservables. We find that brokers steer borrowers to mortgages with longer amortization, while a borrower's own (unobservable) characteristics drive their decision for smaller down payments.
Keywords: D; D4; G; G2; G21; L; L2; 330; Financial institutions; Financial services; Market structure and pricing